Notes on australasian orchids 8 : eight new species of Hymenochilus (Cranichideae: Pterostylidinae) and clarification of two previously described species - Jones, David Lloyd 1944-
Eight new species of Hymenochilus from Australia are described and illustrated. Six of the new species have affinities to (and are here compared with) H. cycnocephalus: H. anemophilus, H. calcicola, H. cymbellus, H. longipes, H. nemoralis and H. pachylus. Hymenochilus anemophilus is shorter (2-8 cm), with dark green strongly veined rosette leaves, crowded dark green flowers, oblong to obovate labellum lamina and, a broader blunter beak on the labellum appendage; H. calcicola is shorter (3-12 cm), crowded green flowers with prominent dark green stripes, ovate petals with a strongly developed basal flange on the anterior side and narrow elliptic labellum lamina with a broad pointed beak on the labellum appendage; H. cymbellusdiffers by its sparser basal rosette with narrower rosette leaves, thinner scapes, flowers with distinct darker green stripes and shallowly saccate lateral sepals that narrow inwards to a distinctly pointed apex; H. lon-gipes differs by its thin-textured rosette leaves, widely spaced darker green flowers with darker green veins, elliptic-obovate labellum lamina and a longer labellum basal appendage which protrudes prominently from the flower in side view; H. nemoralis has longer rosette leaves, thicker scape and darker green flowers with prominent narrow dark green stripes; H. pachylus has thicker rosette leaves, taller, thicker scape, flowers prominently striped, elliptic-obovate labellum lamina and labellum appendage with a short thick beak. Two of the new species have affinities (and are here compared) with H. muticus: H. pagophilus and H. pisinnus. Hymenochilus pagophilus differs by its moderately crowded to crowded flowers, broader, shinier flowers and rectangular-obovate labellum andH. pisinnus differs by its smaller rosette with smaller, narrower leaves, thin-ner scape, smaller flowers, that are often on long pedicels, shorter, shallowly saccate lateral sepals, smaller rhomboid petals...